Measurement of the Z / γ ∗ → τ τ cross section in pp collisions at s = 13 TeV and validation of τ lepton analysis techniques. - Sirunyan A. M.; Tumasyan A.; Adam W.; Ambrogi F.; Asilar E.; Bergauer T.; Brandstetter J.; Brondolin E.; Dragicevic M.; Ero J.; Del Valle A. E.; Flechl M.; et al. (Springer New York LLC, 2018)
A measurement is presented of the Z / γ ∗ → τ τ cross section in pp collisions at s = 13 TeV , using data recorded by the CMS experiment at the LHC, corresponding to an integrated luminosity of 2.3 fb - 1 . The product of the inclusive cross section and branching fraction is measured to be σ ( pp → Z / γ ∗ +X ) B ( Z / γ ∗ → τ τ ) = 1848 ± 12 ( stat ) ± 67 (syst \,+\,lumi) pb , in agreement with the standard model expectation, computed at next-to-next-to-leading order accuracy in perturbative quantum chromodynamics. The measurement is used to validate new analysis techniques relevant for future measurements of τ lepton production. The measurement also provides the reconstruction efficiency and energy scale for τ decays to hadrons + ν τ final states, determined with respective relative uncertainties of 2.2 and 0.9%.
Keywords: Physics and Astronomy (miscellaneous); PROTON-PROTON COLLISIONS; Standard, Model; Atlas detector; MASS; hadron-hadron scattering (experiments); tau lepton; lhc; cms; High Energy Physics - Experiment; PROTON-PROTON COLLISIONS; MODEL HIGGS-BOSON; Atlas detector; Search; PAIR; MASS; LHC; Physics and Astronomy; PAIR; Search; MODEL HIGGS-BOSON; LHC; Engineering (miscellaneous); Physics and Astronomy (miscellaneous); Engineering (miscellaneous)